Are CEOs compensated for value destroying growth in earnings? - Balachandran, Sudhakar; Mohanram, Partha (Review of Accounting Studies, 2010)
Prior research shows that firms generating earnings growth by improving profitability create shareholder value, while firms generating earnings growth through investment destroy value. This paper examines whether compensation committees consider this while determining CEO compensation. We first confirm prior results that growth from increased profitability is perceived by markets to add value while growth from investment does not. While growth from increased profitability is positively associated with compensation, so is growth from investment. The presence of institutional ownership increases the weight on growth from increased profitability, but does not reduce the weight on growth from investment. Further, value-oriented institutional ownership increases the sensitivity of compensation growth to growth from increased profitability and reduces the sensitivity to growth from investment. Contrarily, growth-oriented institutional ownership increases the sensitivity of compensation growth to growth from investment. Our results highlight the importance of understanding the nature of earnings growth in determining executive compensation.